2018
DOI: 10.1177/0886260518814262
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment Experiences, Attachment, Sexual Offending: Testing a Theory

Abstract: The aim of this study was to empirically examine the theoretical model proposed by Grady, Levenson, and Bolder used to explain the relationships between experiencing trauma, attachment styles, and risk factors associated with sexual offending. The specific risk factors tested were emotional, behavioral, and cognitive regulation deficits. The research questions were as follows: (1) What specific childhood traumatic experiences (physical and sexual abuse and/or other domestic trauma events) are associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 88 publications
(127 reference statements)
0
21
0
Order By: Relevance
“…For people who sexually offend, early adversity may have contributed to emotional congruence with children, or hostile feelings or behaviors directed toward women (Levenson et al, 2017). Early relational traumas can lead to a tendency to seek out or exploit others who are more vulnerable and less threatening (Ardino, 2012;Grady et al, 2016;Grady et al, 2018).…”
Section: Early Trauma and Adult Offendingmentioning
confidence: 99%
“…For people who sexually offend, early adversity may have contributed to emotional congruence with children, or hostile feelings or behaviors directed toward women (Levenson et al, 2017). Early relational traumas can lead to a tendency to seek out or exploit others who are more vulnerable and less threatening (Ardino, 2012;Grady et al, 2016;Grady et al, 2018).…”
Section: Early Trauma and Adult Offendingmentioning
confidence: 99%
“…Given that a large meta-analysis designated self-regulation and antisocial traits as supported and promising risks for sexual recidivism (Mann, Hanson, & Thornton, 2010), they may be critical to include as mediators in model testing. Researchers who tested the Grady et al (2017) model (Grady et al, 2018) found that the relationship between maltreatment, attachment, and sexual violence is characterized by both direct and indirect relationships, and may be best explained by intermediated factors such as behavioral regulation. Other studies have revealed how insecure attachments can create vulnerabilities for compensatory reactions—including inhibited emotional, neurological, and cognitive processing—that then contribute to behavioral responses including sexual violence (Marshall & Marshall, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There now exists a substantial amount of literature that demonstrates that ICSCs have experienced significantly more traumatic experiences than either the general population or individuals who have committed nonsexual crimes (e.g., Grady, Yoder, & Brown, 2018; Levenson, Willis, & Prescott, 2014a, 2014b; Yoder, Grady, & Dillard, 2018). Therefore, for many ICSCs, they could be categorized as both a “victim” and an “offender.” This research also demonstrates that not only there is a strong correlation between trauma histories and subsequent sexual offending but also higher rates of trauma are associated with other difficulties such as substance abuse (Levenson, 2016; Levenson & Socia, 2016), interpersonal relationship difficulties, and emotional dysregulation (Grady, Levenson, & Bolder, 2017; Grady & Shields, 2018; Grady et al, 2018). Given their dual identities, many researchers in the field have noted that treatment designed to address recidivism among this population needs to also use a trauma-informed approach (Levenson, 2014, 2017) to address the potential root cause of sexual violence (Grady et al, 2017).…”
Section: Research On Relevant Backgroundsmentioning
confidence: 99%